Determinan Kecukupan Modal Bank Umum Syariah di Indonesia Periode 2015 - 2018 - Luthfi Kurniawan; Marlina Tanjung; Sri Mulyantini (Universitas Pembangunan Nasional Veteran Jakarta, 2021)
AbstractCapital is a basic element in running a business. Capital adequacy for Islamic banking is one of the main indicators for assessing the performance of Islamic banking. This study aims to examine the factors that affect capital adequacy in the Islamic banks in Indonesia. This study will examine the impact of profitability, non-performing financing, liquidity, efficiency, and bank size on capital adequacy in the Islamic banks in Indonesia. The data used in this study is secondary data with the sample collection method using saturated sampling. Thus, the population and sample are the same, namely 14 Islamic Commercial Banks. Data analysis used descriptive statistics and panel data regression analysis with the E-views 10 application and Microsoft Excel 2016. This study found that partially, from the five variables tested, there were four independent variables that had an influence on capital adequacy, namely probability profitability, liquidity, efficiency and bank size. Meanwhile, the non-performing financing variable does not have a significant effect on the capital adequacy of Islamic Banks in Indonesia.AbstrakModal merupakan unsur pokok dalam menjalankan bisnis. Kecukupan modal bagi perbankan syariah menjadi salah satu indikator utama penilaian kesehatan perbankan syariah. Penelitian ini bertujuan untuk menguji faktor-faktor yang memengaruhi kecukupan modal bank syariah di Indonesia. Penelitian ini akan menguji dampak profitabilitas, pembiayaan bermasalah, likuiditas, efisiensi, dan ukuran bank terhadap kecukupan modal bank syariah di Indonesia. Data yang digunakan adalah data sekunder dengan metode pengumpulan sampel menggunakan sampling jenuh, dengan populasi dan sampel sama banyak yaitu 14 Bank Umum Syariah. Teknik analisis data dilakukan menggunakan statistik deskriptif dan analisis regresi data panel dengan aplikasi E-views 10 dan Microsoft Excel 2016. Penelitian ini menemukan bahwa secara parsial, dari lima variabel yang diuji, terdapat empat variabel independen yang memiliki pengaruh terhadap kecukupan modal, yaitu probabilitas, likuiditas, efisiensi dan ukuran bank. Sementara itu, variabel pembiayaan bermasalah tidak berpengaruh signifikan terhadap kecukupan modal bank syariah di Indonesia.